Green Tourism: A Strategy for Realizing an Environmentally-Based Wonderful Indonesia - Firman Sinaga; Komang Shanty Muni Parwati; Febianti; Komang Trigita Juliastari; Firlie Lanovia Amir (Yayasan Inovasi Kemajuan Intelektual, 2025)
The tourism sector is a fundamental pillar of Indonesia's national economy, contributing crucially to Gross Domestic Product (GDP) growth and job creation. However, amidst the acceleration of tourist arrivals, a serious threat emerges in the form of ecosystem degradation that could erode the identity of